Pengaruh Gaya Kepemimpinan dan Komunikasi Terhadap Kinerja Pegawai: Studi Kasus di Kantor Kecamatan Balanipa, Kabupaten Polewali Mandar - Ela Fitri; Magfirah Magfirah; Nur Qamariah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Objective – This study aims to analyze the influence of leadership style and communication on employee performance, both partially and simultaneously, at the Balanipa District Office, Polewali Mandar Regency. Method – The study used a quantitative descriptive approach with a saturated sampling technique. The sample consisted of 39 civil servants and honorary workers. Data were collected through a Likert scale questionnaire (1–5) and analyzed using multiple linear regression, classical assumption tests (normality, multicollinearity, heteroscedasticity), t-test, F-test, and coefficient of determination (R²) with the help of SPSS 26. Results – The results of the study showed that leadership style (t-count = 3.918; sig. = 0.000) and communication (t-count = 4.067; sig. = 0.000) each had a positive and significant partial effect on employee performance. Simultaneously, both variables also had a significant effect (F-count = 42.875 > F-table = 3.25; sig. = 0.000). The R² value of 0.704 indicates that 70.4% of the variance in employee performance is explained by leadership and communication styles, while 29.6% is influenced by other factors not examined. Novelty/Contribution – This study provides empirical evidence from the context of sub-district government in Eastern Indonesia, highlighting that participatory leadership and two-way communication are still underdeveloped yet critical aspects. Implications – Sub-district leaders need to involve subordinates more in decision-making, establish open feedback mechanisms, and conduct regular leadership and communication training to improve employee performance.